Demeanour and Motivation of Animal Husbandry on The Management Implementation of Pigs Farming Business in Kesu’ District, Toraja Utara Regency - A. K., Sarungallo; Suparta, N.; Inggriati, N. W. T. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019, 2019)
The purpose of this study is to find out : 1) the level of application of management of pig farms business; 2) breeders' attitudes and motivations in implementing the management of pig farms business; 3) Analyzing the relationship of characteristics, attitudes and motivations of farmers with the application of management of  pig farms business. This research was conducted in Kesu’ District with 60 respondents.The research using the "Snowball Sampling" method. The type of data used were primary data and secondary data. Primary data were obtained from direct interviews and observations, while secondary data were from literature studies. The analysis that used were quantitative descriptive analysis and Spearman level correlation test. The results showed that the level of application of management of pig farms business in the District of Kesu 'North Toraja Regency in the good category, farmer attitudes are included in the very positive category and farmer motivation is in the very strong category, age and farm ownership are positively related to implementation while the characteristics of education duration and family dependents are not significantly related to the application, and attitudes and motivation are positively related to the implementation of management of pig farms business in Kesu District, North Toraja Regency.   Keywords : Demeanour, Motivatio, Application of Pig Farms Business